2019
DOI: 10.1186/s40425-019-0610-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of M2-like tumor-associated macrophages with a melittin-based pro-apoptotic peptide

Abstract: Background Tumor-associated macrophages (TAMs) are the major component of tumor-infiltrating immune cells. Macrophages are broadly categorized as M1 or M2 types, and TAMs have been shown to express an M2-like phenotype. TAMs promote tumor progression and contribute to resistance to chemotherapies. Therefore, M2-like TAMs are potential targets for the cancer immunotherapy. In this study, we targeted M2-like TAMs using a hybrid peptide, MEL-dKLA, composed of melittin (MEL), which binds preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
131
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 49 publications
3
131
1
Order By: Relevance
“…Macrophages are the most abundant immune cell population present in tumor tissue, and these cells are called tumor-associated macrophages (TAMs) [133,134]. The density of TAMs is reported to be associated with a poor prognosis and positively correlated with tumor progression in several studies.…”
Section: Gal-3 In Tumor-associated Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrophages are the most abundant immune cell population present in tumor tissue, and these cells are called tumor-associated macrophages (TAMs) [133,134]. The density of TAMs is reported to be associated with a poor prognosis and positively correlated with tumor progression in several studies.…”
Section: Gal-3 In Tumor-associated Macrophagesmentioning
confidence: 99%
“…Macrophages are generally categorized as M1 or M2 types, and the majority of TAMs have been shown to exhibit M2-like phenotype in the tumor microenvironment [134]. As a rule, M1 macrophages are considered to have inflammatory and cytotoxic function, whereas M2 macrophages are anti-inflammatory and promoting wound healing.…”
Section: Gal-3 In Tumor-associated Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis and the ability to metastasize involve tumor-associated macrophages (TAMs) in CRC (6,7). M1 and M2 are the major classes of TAMs that display polar effects on tumors (8,9). The former class is activated classically by lipopolysaccharide (LPS) and interferon-γ (IFN-γ) to secrete interleukin-12 (IL-12), IL-1β and cytotoxic inducible nitric oxide synthase (iNOS), among other factors (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested 17 that old age alters macrophage polarization such that the same signals that would produce 18 polarization in younger individuals do not produce differentiated macrophages with all the 19 characteristics generally ascribed to M1 and M2 subtypes (Mahbub et al, 2012). Thus, these 20 results must be interpreted carefully, but an increase in tumor infiltrating macrophages still 21 appears to be a poor survival prognostic in older individuals, which suggests that therapeutics 22 being developed to target the generally negative effects of tumor-associated macrophages 23 (Chanmee et al, 2014), (Poh and Ernst, 2018), (Lee et al, 2019) may be of particular impact in 24 patients of advanced age. 25 A further observation of note is that we find a significant increase in NK cell abundance in GTEx, 1 which we do not identify in TCGA tumor data.…”
mentioning
confidence: 99%